2017
DOI: 10.1111/jspn.12172
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety levels and associated factors among adolescents with type 1 diabetes compared with healthy peers

Abstract: The early identification of social anxiety in adolescents by nurses may reduce possible complications of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
4
1
1
Order By: Relevance
“…The problems experienced by adolescents with their friends are likely to result in a reluctance to carry out their daily diabetes treatment at school (Boztepe, 2012). In another study comparing adolescents with type 1 diabetes and healthy adolescents, it was found that adolescents with type 1 diabetes had high levels of social anxiety and that their social anxiety increased as the process of adaption to diabetes continued (Ceylan & Altay, 2017). In the present study, it was revealed that the adolescents did not inform others about their diabetes to avoid being rejected or perceived differently due to social anxiety, and that their negative perception of insulin treatment consequently increased.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…The problems experienced by adolescents with their friends are likely to result in a reluctance to carry out their daily diabetes treatment at school (Boztepe, 2012). In another study comparing adolescents with type 1 diabetes and healthy adolescents, it was found that adolescents with type 1 diabetes had high levels of social anxiety and that their social anxiety increased as the process of adaption to diabetes continued (Ceylan & Altay, 2017). In the present study, it was revealed that the adolescents did not inform others about their diabetes to avoid being rejected or perceived differently due to social anxiety, and that their negative perception of insulin treatment consequently increased.…”
Section: Discussioncontrasting
confidence: 48%
“…The reason for this is that stigmatization has negative influence on the emotional, behavioral, and social states of these patients as well as on their medical treatment (Browne et al, 2014). Studies in the related literature have demonstrated that fear of stigmatization causes patients with type 1 diabetes to experience anger, stress and social anxiety, to postpone their blood glucose measurements and insulin injections and to have problems with their diets (Boztepe, 2012;Ceylan & Altay, 2017;Jeong, Quinn, Kim, & Martyn-Nemeth, 2018). In addition, it was found that patients who did not comply with insulin treatment had poor glycemic checks and suffered from an increase in complications (Delahanty et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, perceiving the achievement level as moderate was found to increase the social appearance anxiety of early adolescents. In a previous study carried out by Ceylan and Altay (2017), it was determined that the adolescents having good and moderate academic achievement levels and Type I diabetes had more social anxiety when compared to healthy ones. In another study, it was found that the students having higher grade point average had lower social appearance anxiety (Akyol et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In Bezug auf spezifische Angststörungen zeigt sich u. a., dass 12-bis 15-Jährige mit T1DM einen signifikant höheren Wert für soziale Angst (40,14 ± 11,44 [SMD ± Standardabweichung]; gemessen an der Social Anxiety Scale for Adolescents) im Vergleich zu gesunden Gleichaltrigen (33,33 ± 9,34) aufweisen [69]. Bei der Interpretation dieser und weiterer Prävalenzraten sei darauf hingewiesen, dass die Erhebung fast durchgehend über Selbstberichtfragebogen erfolgte, die keine qualifizierte Diagnostik erlauben.…”
Section: Angststörungen Prävalenzunclassified